Site Selection For Wind Energy Farm Using GIS-Based Multi-Criteria Decision Analysis (MCDA)In Qassim Area - Ummhani Idris Ahmed , Manahil. E.E. Mofdal (Migration Letters, 2024)
One of the challenges facing the world in the 21st century is the availability of sustainable and relatively cost-effective renewable energy sources that has lower negative impacts on the environment than fossil fuels. The improvement in human living conditions and world population increase have resulted in high usage and demand of energy. Most of the energy used in the world today is produced from fossil fuels such as oil, natural gas, and coal. The drawbacks of fossil fuel energy include limited stock, environmental pollution, global warming associated with the burning of fossil fuels. The stable increases in the greenhouse’s gases, in particular, CO2 and their contribution to global warming creates a serious concern about the use of fossil fuel and its impact on the environment. This study aims to select suitable sites for wind energy farms in the Qassim region using the integration of Multi-Criteria for Decision Analysis (MCDA) Multi-criteria evaluation. The data used in this study was wind speed and direction, Digital Elevation model, distance from settlements, distance from roads, railways, drainage, land slope, and land uses. The data distances from these features were ranked and weighted. By superimposing these weights, the Model Builder [1]has been built, deriving a map representing the most suitable locations for wind energy in Qassim. The results indicated that the most suitable sites with minimum impacts to the environment, society, and economy as well as conforming with the regulations and generally accepted by the public. The areas that covered with final land suitability index were 98580376.11 km2(14,7%) for Suitable, 61344715.51 km2 (9,1) for very Suitable, 607844.9908 km2(0.1%) for extreme Suitable and 2557421.399 km2 (0.4) for Less Suitable. Results showed that northern part of Qassim region has potential for building wind turbine farm. It is recommended to use suitability model by decision-makers in the plans of energy development.